LA CONTRE-PHÉNOMÉNOLOGIE DE L’AVEUGLE CHEZ JACQUES DERRIDA (The counter-phenomenology of the Blind by Jacques Derrida) - Urszula Idziak-Smoczyńska (Ostium, 2015)
The article deals with Derrida’s project of counter-phenomenology of the blind based on his own exhibition of drawings from the Louvre Museum (26. 10. 1990 – 21. 1. 1991). Writing, drawing and moving with a blind man stick are linked together being each a movement in the dark, driven only by faith. Derrida has focused on drawings of blinds and the art of auto-portraying as an exercise on one’s own blindness. One of such exercises, both technical and spiritual, consists in a deconstructive role of tears capable of covering our eyes with a veil, thus depriving us from mastery over the world and from our sense of justice. At the edges of art, in the visible in praise of the invisible, Derrida discovers an imperative of faith expressed by the answer to the skeptical “do you believe?” [translation modified U.I.S.] which opens the Memoirs of the Blind – “one has to believe”.